2022
DOI: 10.3390/agronomy12040875
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Iron Deficiency Stress on Plant Growth and Quality in Flowering Chinese Cabbage and Its Adaptive Response

Abstract: Iron (Fe) plays an important role in the growth and development of plants. The effects of different Fe concentrations, 1-aminocyclopropane-1-carboxylic acid (ACC), and cobalt chloride (Co2+) treatments on plant growth, quality and the adaptive response to Fe deficiency stress were investigated in flowering Chinese cabbage. The results revealed that Fe deficiency stress inhibited plant growth. The contents of vitamin C, soluble protein, and soluble sugar in leaves and stalks were significantly reduced under Fe … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 27 publications
1
9
0
Order By: Relevance
“…The shoot fresh weight and nutrient quality in early-maturity cultivar ‘Sijiu’ at high RH level reached the marketable weight and quality standard of hydroponic grown plants in the field, and the late-maturity cultivar ‘Chixin’ grew healthy during the whole experiment ( Fig. 3 ) ( Wang et al, 2022 ).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…The shoot fresh weight and nutrient quality in early-maturity cultivar ‘Sijiu’ at high RH level reached the marketable weight and quality standard of hydroponic grown plants in the field, and the late-maturity cultivar ‘Chixin’ grew healthy during the whole experiment ( Fig. 3 ) ( Wang et al, 2022 ).…”
Section: Discussionmentioning
confidence: 94%
“…The chlorophyll pigment contents were examined referring to the method of Wang et al (2022) . Briefly, 0.2 g fresh leaf samples were soaked in 20 mL of an acetone-ethanol mixture (acetone: ethanol = 2:1, v/v) for 24 h at 25 °C in the dark till the leaves turned white.…”
Section: Methodsmentioning
confidence: 99%
“…A research report showed that in Chinese cabbage leaves and stalks the concentration of soluble protein, soluble sugar, and vitamin C was significantly decreased under Fe-deficiency stress conditions, whereas the content of cellulose and nitrate was increased [ 51 ]. The same study found that Fe-deficiency stress significantly lowered net photosynthetic rate and nitrate reductase activity in the leaves.…”
Section: Dynamics Of Iron In the Rhizospherementioning
confidence: 99%
“…Flowering Chinese cabbage is a popular cruciferous vegetable that is commercially distributed in China [ 5 ]. Flowering Chinese cabbage is very popular because it is rich in several nutrients and active phytochemicals, e.g., minerals, dietary fiber, vitamins C and E, glucosinolates, phenolic acids, carotenoids, flavonoids, and anthocyanins, which can be beneficial to human health [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%